Cobalt oxide nanocubes thin film as saturable absorber for generating Q-switched fiber lasers at 1 and 1.5 µm in ring cavity configuration - Al-Masoodi, Ahmed Hasan Hamood; Alani, Ibrahim A.M.; Ahmed, Mahmoud Hazzaa M.; Al-Masoodi, Abtisam Hasan Hamood; Alani, Ahmed A.; Wang, Pengfei; Harun, Sulaiman Wadi (Elsevier, 2018)
We experimentally demonstrate Q-switched fiber lasers based on Ytterbium-doped fiber laser (YDFL) and Erbium-doped fiber laser (EDFL) cavity using cobalt oxide (Co3O4) nanocubes film as a saturable absorber (SA) to operate at 1043.64 nm and 1560.4 nm respectively. This material is embedded into polyethylene oxide (PEO) film to obtain a high nonlinear optical response that can be used for SA application. The Co3O4 nanocubes film was fabricated by a simple processing technique and it has a modulation depth of 4% and saturation intensity of 56 MW/cm2. By incorporating the Co3O4 nanocubes SA into the YDFL cavity, a stable Q-switched pulse train was generated with repetition rate increasing from 60.3 to 86.66 KHz, by increasing the pump power from 144.4 to 165.4 mW. At the pump power of 147.9 mW the pulse width and pulse energy are 4 µs and 154 nJ respectively. The EDFL generates a stable Q-switched pulses with repetition rate of 119.7 KHz, pulse width of 2.4 µs and pulse energy of 6 nJ at maximum pump power of 141 mW. This results propose that cobalt oxide could be a promising broadband SA for all fiber lasers wavelengths at 1 and 1.5 µm.